Informing Geologic CO2 Storage Site Management Decisions under Uncertainty: Demonstration of NRAP's Integrated Assessment Model (NRAP-IAM-CS) Application. (July 2017) - Pawar, Rajesh; Dilmore, Robert; Chu, Shaoping; Zhang, Yingqi; Oldenburg, Curtis; Stauffer, Philip; Guthrie, George; Bromhal, Grant
Abstract: Managing risks at geologic CO2 storage sites requires making decisions based on the quantitative predictions of long-term performance that not only take into account various subsurface hydrologic, geochemical processes and interactions but also the related uncertainties. The US DOE (United States Department of Energy) funded National Risk Assessment Partnership (NRAP) has developed a quantitative approach and a model to predict the long-term behavior of GCS sites. The approach uses an integrated assessment model (NRAP-IAM-CS) that couples reduced order models (ROMs) for various GCS components (such as storage reservoir, wells, seals, and groundwater aquifer) in a stochastic modeling framework that allows for rapid simulations of entire system behavior over thousands of years while probing uncertainties. We demonstrate application of NRAP-IAM-CS using two examples that focus on CO2 leakage and resulting impacts. The examples are used to demonstrate how different uncertain parameters affect overall performance objectives.